Data Communications and Computer Networks for Computer Scientists and Engineers - Duck, Michael and Read, Richard (Chennai,India Pearson Education, 2014)
Written for computer scientists and engineers, this book focuses on the fundamental aspects of data communications and computer networks. Covering networks and their management, transmission technologies, security and encryption, it is suitable for modular courses in data communications, as well as computer science
Include Appendix and Index
Keywords: OSI (Computer network standard) -- Computer networks -- Data transmission systems